Summer and winter browsing affect conifer growth differently: An experimental study in a multi-species ungulate community - Pfeffer, Sabine E.; Singh, Navinder J.; Cromsigt, Joris P.G.M.; Widemo, Fredrik (Forest ecology and management, 2021)
•We studied the growth response of conifers 4.5 years after seasonal fencing.•A full exclusion of deer browsing did not enhance the growth response of conifers.•Scots pine stems reached taller height classes when winter browsing was excluded.•Norway spruce stems reached taller height classes when summer browsing was excluded.•Conifer growth varied due to differences in palatability and plant-competition. Ungulate browsing has been studied for several decades in the northern hemisphere. However, studies have mainly focused on just one or two ungulate species, while rarely contrasting the relative effects of summer and winter browsing. This limits our understanding of the dynamics and effects of browsing in landscapes where ungulate species diversity is increasing. We conducted a seasonal exclosure experiment on former clear-cuts in a multi-species ungulate system in Sweden, to investigate the relative impacts of summer and winter browsing on the conifers Scots pine (Pinus sylvestris) and Norway spruce (Picea abies) at the tree species level. We tested for differences in individual conifer growth and demographic responses between Summer browsing, Winter browsing, No browsing, and Control treatment plots over a 4.5 year experimental period. We defined the demographic response as the distribution of conifers among different height classes. Individual growth rates and demographic responses of both conifer species were similar in the plots with No browsing (year-round exclosures) as in the Control plots with year-round browsing. Plots subject to Summer and Winter browsing differed in terms of their demographic response relative to plots with No browsing and Control plots; more stems reached taller height classes in the Summer and Winter browsing plots with slight differences between the conifer species. We discuss the different responses of Scots pine and Norway spruce considering their differences in palatability and their ability to tolerate plant-plant competition in a multi-species ungulate system, in light of potential associational effects. If fencing is intended to be used as a management practice to mitigate the impacts of deer browsing on conifer growth, our results suggest that a total exclusion of deer does not necessarily enhance conifer growth during the first years of regeneration.